Determinants of Canadian bilateral aid allocations: humanitarian, commercial or political? - Macdonald, Ryan; Hoddinott, John F. (Wiley, 2004)
In this paper we examine the determinants of the allocation of Canadian bilateral aid over the period 1984–2000. We draw on models of donor behaviour that allow us to incorporate humanitarian, commercial and political considerations – the ‘trinity of mixed motives’– that affect Canadian aid. We find that allocations are moderately altruistic. Recipient country human rights and membership in the Commonwealth and La Francophonie also affect aid flows. Most strikingly, our results suggest that Canadian aid flows became less altruistic over this period and commercial motives became increasingly important.